Digital-only banking experience: Insights from gen Y and gen Z - Nila Armelia Windasari; Nurrani Kusumawati; Niken Larasati; Revira Puspasuci Amelia (Journal of Innovation & Knowledge (JIK), 2022)
Currently, most traditional banks provide digital services and the government encourages people to use cashless payments in their everyday life, particularly during the pandemic when the demand for avoiding physical encounters is getting higher. There is a growing trend in the development of digital-only banks, a fully virtual bank without individual physical branches where all banking activities operate through mobile applications. Fully virtual operations change how individuals experience the service, and subsequently, their consumption and financial habits. This research explores the experiential factors affecting digital-only banking services among the generation Y and Z. A mixed-method approach was applied using semi-structured interviews and empirical surveys. We interviewed 20 respondents to explore customers' experiences, followed by a survey to test the hypotheses developed from the proposed factors to 402 respondents aged 17-35 who used digital banking in the past six months. We analyzed the relationship of eight variables when using digital-only banking: economic value, ease of use, social influence, firm reputation, promotion, features, curiosity, and reward. Results show that all variables except curiosity and sales promotion significantly impact intention to use digital-only banking. Creating an attractive and simple digital banking interface is important to support an ease-of-use experience for customers. However, to ensure positive customer experiences, other factors must be applied, such as rewards, unique features, and positive word-of-mouth.
Keywords: M31; 650; Customer experience; Digital service; Digital-only banking; Generation Y; Generation Z; Virtual banking